Educational Technology-Based Strategies for The Internationalization of Islamic Higher Education in Indonesia and Brunei Darussalam - Samsul Susilawati; Triyo Supriyatno; Ahmad Fatah Yasin; Abdulloh Chakim; Zuhrotul Hani’ah; Candra Avista Putri; Ahmad Sabri (Universitas Pesantren Kh abdul Chalim Mojokerto, 2025)
This study aims to analyze the strategy of internationalization of Islamic higher education through the use of educational technology towards achieving a world-class university status in two universities: the State Islamic University of Maulana Malik Ibrahim, Malang, Indonesia, and Sultan Syarif Ali University, Brunei Darussalam. This paper uses a case study approach with a qualitative method. Data collection was carried out through interviews, observations, and documentation. Regarding data analysis, the researcher reduces the data, presents it, and draws conclusions. Verification is used for comparison between case studies. Additionally, this study employs triangulation of sources and methods to validate its findings. The results of the study show that the development strategy of Internationalization of Islamic Higher Education with the use of educational technology aims to prepare graduates who are relevant to current needs and able to compete in the era of globalization with the following steps: integrating technology in the learning process through educational technology using Learning Management System, E-learning, blended learning, and holding conferences with the system hybrid, online learning platform and digitization of administrative systems, conducting quality evaluations and audits, developing international collaboration programs and adapting the curriculum to global standards, developing networks between universities in Asia in strengthening international relations and cooperation.